Human Body Model for Channel Characterization Based on Ray-Tracing - Lei Xiong; Haiyang Miao; Zhiyi Yao (International Journal of Antennas and Propagation)
The propagation channel around human body will fluctuate due to the body effects, so it is essential to investigate the body channel. As an important method of channel modeling, ray-tracing (RT) is affected by the human body model. In this paper, a realistic human body is modeled with the idea of greedy algorithm. Based on the RT simulation and measurement results of path loss (PL), we derive the approximate shapes of the torso, head, arms, and legs, and propose a reference human body model whose credibility and accuracy have been verified at 2.4 GHz and 60 GHz. These results prove that the simulation results based on the reference human body model are in good agreement with the measurement values. In addition, the reference human body model can be adjusted according to the realistic dimension data of body.